Saint Martin in Polish local self-government heraldry - Piechocka-Kłos, Maria (Forum Teologiczne, 2022)
Saint Martin is a very popular character in the Christian tradition. His life and deeds have had a considerable impact on successive generations of Christians, beginning with the Middle Ages and he is still present in the minds of believers. The popularity of this saint in Poland and Europe is reflected in many names of churches, parishes, chapels, altars as well as in art, names and heraldry. This paper presents selected local self-government coats of arms displaying an image of St. Martin or attributes associated with him. The full figure of St. Martin in Polish local self-government heraldry can be found on the coats of arms of five rural communes (the communes of Biskupice, Drużbice, Granowo, Mochowo and Wiśniowa), the coats of arms of two urban communes (the commune of Jawor, the town and commune of Pacanów) and the coat of arms of an urban quarter (Słocina – currently a quarter of Rzeszów, earlier – until 1954 – a commune). Only one of these, i.e. the coat of arms of the commune of Poświętne, refers to St. Martin by objects associated with him. Heraldic representations of Martin of Tours can be found, for example, in Germany, especially in Hesse, Bavaria, Rhineland-Palatinate, Mainz, but also in Czechia, Austria, Slovakia, Finland and Ukraine.